2014
DOI: 10.1515/jpem-2013-0385
|View full text |Cite
|
Sign up to set email alerts
|

Gut hormone profiles in preterm and term infants during the first 2 months of life

Abstract: Serum concentrations of different gut hormones changed postnatally in their specific ways in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…Karakosta et al calculated gender-specific reference intervals for leptin levels in cord blood in 398 healthy neonates in Crete and found that females had higher levels of this hormone than males [25]. Leptin levels have been shown to be consistently higher in females than in males later in life [26], [27]. We hypothesize that these differences are related to differences in body composition or hormone levels in males and females.…”
Section: Discussionmentioning
confidence: 78%
“…Karakosta et al calculated gender-specific reference intervals for leptin levels in cord blood in 398 healthy neonates in Crete and found that females had higher levels of this hormone than males [25]. Leptin levels have been shown to be consistently higher in females than in males later in life [26], [27]. We hypothesize that these differences are related to differences in body composition or hormone levels in males and females.…”
Section: Discussionmentioning
confidence: 78%
“…Three gut hormones released in response to feeding and with effects on gut growth and function are gastrin released from gastric G cells, glucose-dependent insulin-trophic hormone (GIP) from (proximal) intestinal K cells and glucagon-like peptide 2 (GLP-2) from (distal) intestinal L cells. Preterm infants show elevated levels of these GI hormones, compared with term infants and adults, and they are sensitive to enteral stimuli (1,16,27). During total parenteral nutrition (TPN), in the absence of enteral food, administration of the gut tropic hormone, GLP-2, markedly improves gut growth and adaptation in preterm and term pigs (9,36,38), but the role of this and other GI hormones on later GI development remains unknown.…”
mentioning
confidence: 99%
“…In line with these statements, some studies demonstrated that a rapid weight catch-up in early infancy, often detected in premature and SGA children, may affect both, the degree of adiposity and the IR, as well as leptin concentrations [55]. Toprak et al [56] and Kawamata et al [57] reported an increase in leptin levels in preterm infants after 30 days of life and aftersix weeks of follow-up, respectively, accompanied by an increase in body weight and subcutaneous AT [56]. However, in another study [58], leptin levels did not differ significantly among children born preterm or full-term, and no association between leptin and catch-up growth was observed.…”
Section: Discussionmentioning
confidence: 88%